The professional identity of the Iranian teachers: a case of professional practices. Issue 3 (27th May 2022) - Aliakbari, Mohammad; Sadeghi, Setayesh
ABSTRACT: The study intended to explore teachers' professional identity in terms of teachers' perceptions of their practices. The study employed mixed-methods design, including 80 survey participants and 19 interviews with teachers. In the quantitative section, teachers' perceptions of their commitment to professional practices and how their perceptions were influenced by variables such as gender, age, educational degree, and teaching experience were explored. The results of descriptive statistics revealed that teachers were strongly committed to professional practices. Additionally, data analysis indicated significant differences in teachers' perceptions with reference to age and teaching experience, but teachers' gender and education degree did not appear significant. The qualitative findings revealed that teachers mainly tended to exercise professional practices of personal growth and interactional practices, and considered 'teaching/learning materials' as an important contributing factor in implementing professional practices. The data also showed that teachers' professional identity practices were influenced by contextual factors and macro-political policies.